10 Endogenous and exogenous loading of extracellular vesicles for therapeutic delivery of renin-angiotensin system peptides in cardiomyocyte hypertrophy. (26th March 2018) - Downie, LS; Work, LM; Nicklin, SA
Abstract : Introduction: The RAS peptide angiotensin II (AngII) mediates cardiac hypertrophy. The counter-regulatory RAS axis peptide Angiotensin 1–7 [Ang-(1–7)] inhibits cardiomyocyte hypertrophy. EVs were purified from cardiomyocytes ± treatment with AngII or Ang-(1–7) to assess cardiomyocyte hypertrophy. EVs were loaded with Ang-(1–7) via electroporation for therapeutic delivery. Methods: H9c2 cardiomyocytes were untreated (control) or treated with AngII or Ang-(1–7). EVs were isolated from conditioned media by differential ultracentrifugation, characterised by BCA, western immunoblot, Nanosight and TEM and incubated with recipient cardiomyocytes. Next, cells were stained with F-Phalloidin actin and area measured. Gene expression of hypertrophy marker brain natriuretic peptide (BNP) was assessed by qRT-PCR. Control EVs were electroporated in the presence of Ang-(1–7) and levels determined by ELISA. Results: H9c2 cardiomyocyte-derived EV size was 101.0±2.4 nm and EV markers CD63 and TSG-101 were consistently detected. EVs from AngII treated cardiomyocytes significantly increased recipient cardiomyocyte area compared to control EVs [control: 3291.1±90.1 µm 2 vs AngII:5252.3±125.4 µm 2 ; p<0.001] and significantly increased BNP expression [p<0.017]. EVs isolated from Ang-(1–7) treated H9c2 cardiomyocytes significantly reduced AngII induced hypertrophy in recipient cardiomyocytes [AngII +Control EVs:5566.3±139.0µm 2 vs AngII +Ang-(1–7) EVs:4212.7±132.1 µm 2 ; p<0.01]. Electroporation loaded EVs with Ang-(1–7) [naïve EVs:0.0 pg/mL vs Ang-(1–7) EVs:342.3±9.1 pg/mL; p<0.001]. Ang-(1–7) loaded EVs significantly reduced AngII induced hypertrophy in recipient cardiomyocytes [Naive EVs:4641.2±35.3µm 2 vs Ang-(1–7) EVs:2758.4±20.1µm 2 ; p<0. 001]. Conclusion: EVs isolated from AngII treated H9c2 cardiomyocytes stimulate recipient cardiomyocyte hypertrophy. EVs isolated from Ang-(1–7) treated cardiomyocytes inhibit hypertrophy. Furthermore, EVs exogenously loaded with Ang-(1–7) inhibit cardiomyocyte hypertrophy. These findings have implications for understanding the role of the RAS and EV function in cardiomyocytes.